Effect of phytase from aspergillus niger on plant growth and mineral assimilation in wheat (Triticum aestivum Linn.) and its potential for use as a soil amendment - Gujar, Pradnya D.; Bhavsar, Kavita P.; Khire, Jayant Malhar (Journal of the Science of Food and Agriculture, 2013)
Background Extensive use of non-replenishable phosphate reserves as phosphate supplements in agriculture and animal feed poses a threat for environmental pollution and necessitated a search for alternative phosphate sources. Unlocking the phytate phosphorus using microbial phytase can provide an ecofriendly solution in agriculture. The aim of the present work was to evaluate the effect of phytase from Aspergillus niger NCIM 563 in degradation of phytate phosphorus to benefit plant nutrition and soil amendment in comparison with chemical fertilizers. Results An enzyme dose of 12 IU was sufficient to hydrolyze phytate and increase assimilation of phosphorus by about 74%. Phytase supplementation leads to increase in shoot:total length ratio by about 200%, indicating its growth-promoting effect. Consistency in phytase-induced growth was reflected at pot and tray levels, wherein shoot:total length ratio was observed to be 2.01 and 2.12 respectively. Mineral assimilation due to phytase was more efficient as compared to chemical fertilizers, thus overcoming the constraints of practicability and economics in the agriculture industry. Phytase was efficient in reducing the phytic acid content of soil by about 30% while simultaneously increasing the phytate phosphate availability by 1.18-fold. Conclusion Phytase from A. niger showed improvement in phytate phosphorus and mineral availability. Besides a plant growth-promoting effect, reduction in use of chemical fertilizers and soil improvement could be achieved simultaneously for maintaining the sustainability of agriculture. (c) 2012 Society of Chemical Industry
Keywords: mineral assimilation; Phytase; phytate degradation; plant growth promotion; soil amendment

Rhizobacterial consortium mediated aroma and yield enhancement in basmati and non-basmati rice ( Oryza sativa L.) - Dhondge, Harshal V.; Pable, Anupama A.; Barvkar, Vitthal T.; Dastager, Syed G.; Nadaf, Altafhusain B. (Journal of Biotechnology, 2021)
Basmati and non-basmati rice varieties are commercially important. Aromatic rice varieties are low yielding and recently depletion in aroma is observed due to the shift towards modern agriculture. Therefore, it is necessary to restore the aroma and increase the yield through sustainable agriculture. The use of microbial bioinoculants is one of the promising ways to achieve these targets. With these objectives, rhizospheric bacterial strains Enterobacter hormaechei (AM122) and Lysinibacillus xylanilyticus (DB25) having the property of synthesizing 2acetyl-1-pyrroline (2AP) were isolated from the rhizosphere of two aromatic rice varieties, Ambemohar-157 and Dehradun Basmati respectively and their effect on plant growth, aroma and yield enhancement under mono-inoculation and consortium conditions was analyzed. The bacterial inoculum in consortium resulted in significant improvement in vegetative growth, yield and 2AP content over mono inoculation and control. The study highlights the potential of E. hormaechei and L. xylanilyticus in plant growth, yield and aroma enhancement in basmati and non-basmati rice varieties. These strains can be taken up further for developing a commercial bioformulation.
Keywords: 2-Acetyl-1-pyrroline; Basmati rice; Non-basmati rice; plant growth promotion; Rhizosphere; yield